A tribute to Almarhum Dr. Osman Chuah - Abdul Razak, Mohd Abbas (Department of Communication, Kulliyyah of Islamic Revealed Knowledge and Human Sciences, 2021)
A Tribute to Almarhum Dr. Osman Chuah In the morning of 25th July 2021, though it was a Sunday, while I was at my office working on one of my academic papers, the sad news on the demise of Dr. Osman reached my ears. For a moment, I became motionless and stopped writing. The next one hour or more my mind started to reflect on the good times my friends Prof Sikandar, Dr Shuhaimi and I had with this great man. Started as a BA student of IIUM, Dr. Osman obtained highest academic degree of PhD while serving as a lecturer at this prestigious university. Dr. Osman whom I first came to know in 2011, had a long standing teaching career at the Department of Usuluddin and Comparative Religion, KIRKHS, IIUM. Despite of being categorized as a physically challenged person, Dr. Osman was spiritually strong and intellectually prolific when it comes to scholarly publication and contribution. As a member of the faculty, he was a team player who never preferred to take the glory for himself. As a teacher of Comparative Religion, he was well versed on Confucianism and Buddhism. In addition, he was also specialized in issues related to new converts/reverts to Islam. The issues on converts no one was better learned in the Kulliyyah other than Dr. Osman who had an immense personal experience as a convert himself. As a Murabbi, he was very much liked by his colleagues and students. Much of his scholarly works were produced in the quiet ambience of his modest office at IIUM. At many occasions, I have found him doing two- finger typing, only stopping intermittently to sip his favorite Chinese Tea. Besides teaching, he also served as an advisor to several Da’wah organizations in Malaysia. After his retirement, Dr. Osman’s health started to deteriorate from bad to worse. During the last few years of his life he was a housebound man, only going out to meet the doctor’s appointment. During the many house visits we had after his retirement, though he was in pain, he would with much enthusiasm request us to do research and suggest on how to eliminate the sufferings of the Ummah in many parts of the world. Though Dr. Osman was struggling with his ailments, his final departure was a peaceful one with a brimful of smile on his lips in the presence of his beloved wife. His burial ceremony was a simple one due to Covid-19 lockdown in the country. Alhamdulillah, I was among the six who were allowed to assist in putting Dr. Osman in his final resting place at Ukay Perdana. During that occasion, I took the opportunity to convey the Ta’ziah (condolences) from my research team and on behalf of the KIRKHS and IIUM community. Though it was a small gathering, in my conviction I felt that there must be countless Malaikah (angels of Allah) were there to welcome him to the other side of life. Dr. Osman’s contribution, dedication and humility make him the classic personification of a humble scholar of Islam. For all his remarkable contributions, we pray that his blessed soul will placed among the Solihins (the righteous) and those who are nearest to Allah the Almighty, ameen! Dr. Mohd Abbas Abdul Razak International Islamic University Malaysia 8th August, 2021